2022
DOI: 10.3389/fpls.2021.809069
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of the Dominant Virus Resistance Gene AV-1pro From Asparagus prostratus to Chromosome 2 of Garden Asparagus A. officinalis L.

Abstract: An introgression breeding programme was carried out to transfer the virus resistance gene AV-1pro from the wild species Asparagus prostratus to the garden asparagus Asparagus officinalis. Serious crossing barriers caused by genetic distance and different ploidy levels of the crossing parents have been overcome using embryo rescue for the F1, BC1, and BC2 generations. The male and female fertility was widely restored in BC2 and was shown to be comparable to the cultivated asparagus. Five AV-1 resistant diploid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Garden asparagus ( Asparagus officinalis L.) is the most traditionally significant and best-known plant in Asparagaceae owing to its economical, nutritional, and medical value ( Norup et al., 2015 ; Zhang et al., 2022 ; García et al., 2023 ). Over the past 20 years, the acreage of this plant has expanded significantly worldwide, especially in China ( Nothnagel et al., 2022 ). At present, the main commercial asparagus varieties are diploid varieties that originate from the original “Violet Dutch.” ( Knaflewski, 1996 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Garden asparagus ( Asparagus officinalis L.) is the most traditionally significant and best-known plant in Asparagaceae owing to its economical, nutritional, and medical value ( Norup et al., 2015 ; Zhang et al., 2022 ; García et al., 2023 ). Over the past 20 years, the acreage of this plant has expanded significantly worldwide, especially in China ( Nothnagel et al., 2022 ). At present, the main commercial asparagus varieties are diploid varieties that originate from the original “Violet Dutch.” ( Knaflewski, 1996 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, expanding the genetic diversity is a prominent goal in asparagus breeding. Interspecies hybridization is an important method for enriching genetic diversity and cultivating new cultivars ( Takeuchi et al., 2018 ; Moreno-Pinel et al., 2021 ; García et al., 2022 ; Nothnagel et al., 2022 ). However, at present, the genetic relationship among many plants in the genus Asparagus remains unknown, which has hindered advances in the genetics and breeding of A. officinalis ( Kubota et al., 2012 ; Mousavizadeh et al., 2021 ; García et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The successful implementation of MAS for disease resistance is dependent on knowledge of the genetic architecture of host disease resistance. Studies have shown that MAS is most suitable for vertical resistance, which is often monogenic or oligogenic, while GS might be more suitable for quantitative or horizontal disease resistance (Miedaner & Korzun, 2012;Olatoye et al, 2019). Therefore, deciphering the genetic architecture of host resistance to a particular pathogen is essential for informed decision-making in MAB.…”
Section: Core Ideasmentioning
confidence: 99%
“…Garden asparagus (Asparagus officinalis L.) is the most traditionally significant and best-known plant in Asparagaceae owing to its economical, nutritional, and medical value (Norup et al, 2015;Zhang et al, 2022;Garcıá et al, 2023). Over the past 20 years, the acreage of this plant has expanded significantly worldwide, especially in China (Nothnagel et al, 2022). At present, the main commercial asparagus varieties are diploid varieties that originate from the original "Violet Dutch."…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, expanding the genetic diversity is a prominent goal in asparagus breeding. Interspecies hybridization is an important method for enriching genetic diversity and cultivating new cultivars (Takeuchi et al, 2018;Moreno-Pinel et al, 2021;Garcıá et al, 2022;Nothnagel et al, 2022). However, at present, the genetic relationship among many plants in the genus Asparagus remains unknown, which has hindered advances in the genetics and breeding of A. officinalis (Kubota et al, 2012;Mousavizadeh et al, 2021;Garcıá et al, 2022).…”
Section: Introductionmentioning
confidence: 99%